The case for development of a core outcome set (COS) and supplemental reporting guidelines for influenza vaccine challenge trial research in swine - Keay, Sheila; Alberts, Famke; O’Connor, Annette M.; Friendship, Robert; O’Sullivan, Terri; Poljak, Zvonimir (Frontiers in Veterinary Science, 2025)
Previously, we systematically reviewed more than 20 years of influenza vaccine challenge trial research in pigs to answer the question, “does vaccinating sows protect offspring?” Overall, most studies were well designed but clinical heterogeneity made between-study comparisons challenging. Studies varied by samples, outcomes, and assays selected for measurement. Additionally, data essential for inclusion of findings in meta-analyses were often insufficiently reported and as a result, summary effect measures were either not derived or were not meaningful. Clinical heterogeneity and reporting issues complicate and limit what can be learned cumulatively from research and both represent two types of avoidable research waste. Here, we illustrate each concern using data collected tangentially during the systematic review and propose two corrective strategies, both of which have broad applicability across veterinary intervention research; (i) develop a Core Outcome Set (COS) to reduce unnecessary clinical heterogeneity in future research and (ii) encourage funders and journal editors to require submitted research protocols and manuscripts adhere to established reporting guidelines. As a reporting corollary, we developed a supplemental checklist specific to influenza vaccine challenge trial research in swine and propose that it is completed by researchers and included with all study protocol and manuscript submissions. The checklist serves two purposes: as a reminder of details essential to report for inclusion of findings in meta-analyses and sub-group meta-analyses (e.g., antigenic or genomic descriptions of influenza vaccine and challenge viruses), and as an aid to help synthesis researchers fully characterize and comprehensively include studies in reviews.